2012
DOI: 10.3329/bjvm.v3i2.11395
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ivermectin (Pour on Formulation) Against Ectoparasites in Sheep

Abstract: The research has been carried out from February to March 2005 on 20 sheep (infested and non infested with ectoparasites) of both sexes aged upto 3 to 4 years at the animal house of Veterinary Clinic, Bangladesh Agricultural University, Mymensingh to study the efficacy of ivermectin pour on (Ivermec® Pour on, Ethical Drugs Ltd., Dhaka, Bangladesh) against ectoparasites and its effect on certain haematological (Hb, TEC and PCV) parameters and body weight gain. Fifteen sheep heavily infested with different ectopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The hair coat of the infected control group A became more and discolored. This result was in agreement with the findings of Razu et al (2010) and Hanif et al (2005). The efficacy of three herbal and one patent drug against mange infestation in goat.…”
Section: Discussionsupporting
confidence: 93%
“…The hair coat of the infected control group A became more and discolored. This result was in agreement with the findings of Razu et al (2010) and Hanif et al (2005). The efficacy of three herbal and one patent drug against mange infestation in goat.…”
Section: Discussionsupporting
confidence: 93%
“…The overall in-vivo e cacy of 1% Ivermectin was 81%, which is below the standard for in-vivo trials set limit (98-100%), suggestive of drug resistance. This result is far lower than the ndings of [49], who reported that Ivermectin was 100% effective against sheep lice based on pour on formulations [19,47,50]. The probable reason why reduced e cacy of 1% Ivermectin injection against Bovicola ovis could be associated with prolonged and inappropriate use of the drug, the frequent application of 1% Ivermectin drug with the same brand without rotation with other insecticide classes.…”
Section: Discussionmentioning
confidence: 84%
“…Innovative antiparasitic drugs have been developed and proposed for veterinary practice, having a broad spectrum of action against several animal parasites. These drugs were based on anthelmintics from the class of macrocyclic lactones with high activity against nematodes and ectoparasites of animals [ 4 ]. Another promising anthelmintics class is benzimidazoles, which are active against a wide range of helminths [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%